Comparing the effect of high-intensity interval exercise and voluntary exercise training on cognitive functions in rats - Sezer, Tuğba; Okudan, Nilsel; Belviranli, Muaz (Neuroscience letters, 2024)
It is known that exercise increases brain-derived neurotrophic factor (BDNF) levels in the hippocampus, the brain region responsible for learning and memory, resulting in improved cognitive functions and learning processes. However, it is claimed that different types of exercise cause different responses in the brain. It is thought that lactate and osteocalcin secreted in response to exercise are associated with an increase in BDNF levels. However, there are not enough studies on this subject. This study aimed to compare the effects of high-intensity interval training (HIIT) and voluntary exercise training on cognitive performance and molecular connections. Male rats were randomly divided into control, voluntary exercise training and HIIT groups. The voluntary exercise group had free access to the voluntary wheel for 8 weeks. The HIIT group performed HIIT on the treadmill 3 days a week for 8 weeks. The rats underwent open field (OF), elevated plus maze (EPM) and Morris water maze (MWM) tests 24 h after the last exercise training. Then, after blood was drawn under anesthesia, the rats were sacrificed and their hippocampus tissues were separated. Glucocorticoid and BDNF levels in the blood were evaluated by enzyme-linked immunosorbent assay (ELISA), and osteocalcin and BDNF expressions in the hippocampus were evaluated by real-time quantitative reverse transcription-polymerase chain reaction (RT-PCR). Neither voluntary exercise training nor HIIT had any significant effect on behavioral parameters assessed by OF, EPM and MWM tests. However, BDNF expression in hippocampus tissue was higher in the HIIT group than in the control group. In addition, osteocalcin expression in hippocampus tissue was higher in the HIIT and voluntary exercise groups than in the control group. In conclusion, according to the findings we obtained from this study, although it does not have a significant effect on cognitive functions, the effect of HIIT on brain functions seems to be more effective than voluntary exercise.